About the usefulness of contact precautions for carriers of extended-spectrum beta-lactamase-producing Escherichia coli. Issue 1 (December 2015) - Zahar, Jean-Ralph; Poirel, Laurent; Dupont, Claire; Fortineau, Nicolas; Nassif, Xavier; Nordmann, Patrice
Abstract Background Extended-spectrum β-lactamases producingEscherichia coli (ESBL-E) are increasingly identified in health care facilities. As previously done for the control of methicillin-resistantStaphylococcus aureus, many hospitals have established screening strategies for early identification of patients being carriers of ESBL producers in general and ESBL-E in particular, and have implemented contact precautions (CP) for infected and colonized patients. Methods The incidence of ESBL-E has been compared retrospectively between two French university hospitals (A and B) with different infection control policies over a 5-year long period of time (2006–2010). Results While hospital A only implemented standard precautions after identification of patients colonized with ESBL-E, hospital B recommended additional CP. During the period of the study, the ESBL-E incidence rate significantly increased in both hospitals, but no significant difference was observed between the two hospitals. Conclusions This observational study did not reveal that additional CP measures had a greater impact on the incidence of ESBL-E in hospital settings.